2008
DOI: 10.1182/blood-2007-09-111369
|View full text |Cite
|
Sign up to set email alerts
|

The Modifier of hemostasis (Mh) locus on chromosome 4 controls in vivo hemostasis of Gp6−/− mice

Abstract: Platelet glycoprotein VI (GPVI) is a key receptor for collagens that mediates the propagation of platelet attachment and activation. Targeted disruption of the murine gene Gp6 on a mixed 129 ؋ 1/ SvJ ؋ C57BL/6J background causes the expected defects in collagen-dependent platelet responses in vitro. The extent of this dysfunction in all Gp6 ؊/؊ mice is uniform and is not affected by genetic background. However, the same Gp6 ؊/؊ mice exhibit 2 diametrically opposed phenotypes in vivo. In some mice, tail bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…These results are consistent with at least some published studies (see Discussion) in which Par4 and GPVI mutants were studied separately 1618,26,29 . Thus, in contrast to thrombin-signaling, GPVI signaling was unnecessary for normal thrombus formation when other platelet signaling pathways were left intact.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with at least some published studies (see Discussion) in which Par4 and GPVI mutants were studied separately 1618,26,29 . Thus, in contrast to thrombin-signaling, GPVI signaling was unnecessary for normal thrombus formation when other platelet signaling pathways were left intact.…”
Section: Resultssupporting
confidence: 93%
“…Some variability might be due to different means of achieving GPVI loss of function, e.g., FcRγ mutation and antibody-induced GPVI shedding might have effects beyond loss of GPVI signaling. Variability across studies of Gp6 nulls may also be due in part to different genetic backgrounds 26 . The Gp6 and Par mutant mice examined in this study had been backcrossed >7 times into a C57BL6 background and littermates were compared.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Cheli et al [25] using the same mixed GPVI −/− mice on the 129/SvJ x C57BL/6 background identified a Modifier of hemostasis ( Mh ) locus on chromosome 4 that correlated with the extreme but transient dichotomy in tail bleeding time (tBT) seen in the earlier generations of these mice. A modest correlation was also observed in the in vivo ferric chloride-induced carotid artery injury model.…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, evidence is emerging that the function of collagen and/or collagen receptors on platelets may be subjected to the modifying effects of still unknown gene products. 41 Here, to highlight the role of ␣2␤1, we have used acid-soluble collagen type I, which does not exist as such in vivo but is composed of an assembly of fibrils in a helical configuration that may mimic the properties of the spiraled collagens identified in normal and pathologic tissues. 42 To extend the significance of our findings, we have also used collagen type VI, which platelets contact directly when the subendothelial matrix is exposed or, associated with collagen type I and III, when lesions reach deeper layers of the vessel wall.…”
mentioning
confidence: 99%